Orientamenti emergenti nella ricerca educativa: i metodi misti - Picci, Patrizia (Studi sulla Formazione/Open Journal of Education, 2013)
In the debate about the quantitative and qualitative methodologies, that marked for many years the research, nowadays there is a new orientation, amenable to the formula of “mixed methods”. It’s not clear if the expression is only an label that masks a generic eclecticism of if it’s a epistemologically founded way to overcome the traditional dichotomy. The actual debate is an occasion to increase awareness and transparency about the researcher’s methodological choice. This text present a brief panoramic of diffusion of mixed methods in the international scenery, hinting some attempts of systematisation of the different and complex types of inquiry.